Spy x family. 4 - Endō, Tatsuya, 1980- (Spy x family, 2021)
"Master spy Twilight is unparalleled when it comes to going undercover on dangerous missions for the betterment of the world. But when he receives the ultimate assignment--to get married and have a kid--he may finally be in over his head!... The Forgers look into adding a dog to their family, but this is no easy task--especially when Twilight has to simultaneously foil an assassination plot against a foreign minister! The perpetrators plan to use trained dogs for the attack, but Twilight gets some unexpected help to stop these terrorists."--Provided by publisher.